Antioxidant Mechanisms in the Neuroprotective Action of Cemtirestat: Studies in Chemical Models, Liposomes and Rat Brain Cortical Slices. (1st September 2020) - Soltesova Prnova, Marta; Medina-Campos, Omar Noel; Pedraza-Chaverri, José; Colín-González, Ana Laura; Piedra-García, Francisco; Rangel-López, Edgar; Kovacikova, Lucia; Ceylan, Asli; Karasu, Cimen; Santamaria, Abel; Stefek, Milan
Graphical abstract: Highlights: Direct iron reducing capacity of cemtirestat was proved. Cemtirestat scavenged peroxyl radicals, hydrogen peroxide and superoxide. Cemtirestat inhibited liposome peroxidation more efficiently than melatonin. Neuronal cell damage induced by quinolinic acid was attenuated by cemtirestat. Cemtirestat restored thiol-disulfide homeostasis by releasing free glutathione. Abstract: Neuroprotective action of the novel aldose reductase (AR) inhibitor cemtirestat (CMT), 2-(3-thioxo-2 H -[1, 2, 4]triazino[5, 6- b ]indol-5(3 H )-yl)acetic acid, was recently proved in experimental rat models of diabetes. The in vivo results indicated that the antioxidant activity of this compound might have participated on its effects. The aim of this study was to explore in a greater detail the putative antioxidant mechanisms potentially involved in CMT mediated neuroprotection. Antioxidant efficacy per se of CMT was proved by a ferric reducing antioxidant power (FRAP) test and CMT was found to scavenge reactive oxygen species (ROS) generated in water phase chemically with decreasing efficacy as follows ROO > H2 O2 > O2 − . Studies in liposomes revealed the ability of CMT to inhibit lipid peroxidation more efficiently than melatonin, yet less effectively than Trolox. In the rat brain cortical slices, CMT reduced the loss of cell viability/mitochondrial function induced by quinolinic acid (QUIN), and inhibited lipid peroxidation. In addition, CMT normalized the GSH/GSSG ratio which could be explained, at least partially, by the ability of this compound to release free GSH from the pool of endogenously bound disulfides. Neuronal cell damage induced by QUIN or H2 O2 was reduced by CMT as proved by significant drop in propidium iodide incorporation into cells. On balance then, our results corroborated the notion of a multifunctional action of CMT as a drug combining AR inhibition with direct antioxidant and ROS scavenging activity. Moreover, the ability of CMT to restore thiol-disulfide homeostasis was proved.